Frustration of Negative Capacitance in Al2O3/BaTiO3 Bilayer Structure - Kim, Yu Jin; Park, Min Hyuk; Lee, Young Hwan; Kim, Han Joon; Jeon, Woojin; Moon, Taehwan; Do Kim, Keum; Jeong, Doo Seok; Yamada, Hiroyuki; Hwang, Cheol Seong (NATURE PUBLISHING GROUP, 2016)
Enhancement of capacitance by negative capacitance (NC) effect in a dielectric/ferroelectric (DE/FE) stacked film is gaining a greater interest. While the previous theory on NC effect was based on the Landau-Ginzburg-Devonshire theory, this work adopted a modified formalism to incorporate the depolarization effect to describe the energy of the general DE/FE system. The model predicted that the SrTiO3/BaTiO3 system will show a capacitance boost effect. It was also predicted that the 5 nm-thick Al2O3/150 nm-thick BaTiO3 system shows the capacitance boost effect with no FE-like hysteresis behavior, which was inconsistent with the experimental results; the amorphous-Al2O3/epitaxial-BaTiO3 system showed a typical FE-like hysteresis loop in the polarization - voltage test. This was due to the involvement of the trapped charges at the DE/FE interface, originating from the very high field across the thin Al2O3 layer when the BaTiO3 layer played a role as the NC layer. Therefore, the NC effect in the Al2O3/BaTiO3 system was frustrated by the involvement of reversible interface charge; the highly stored charge by the NC effect of the BaTiO3 during the charging period could not be retrieved during the discharging process because integral part of the polarization charge was retained within the system as a remanent polarization.
Keywords: FERROELECTRICITY; ENHANCEMENT; THICKNESS